Pre-Clinical Assessment of SAR442257, a CD38/CD3xCD28 Trispecific T Cell Engager in Treatment of Relapsed/Refractory Multiple Myeloma - Anna Luise Grab; Peter S. Kim; Lukas John; Kamlesh Bisht; Hongfang Wang; Anja Baumann; Helgi Van de Velde; Irene Sarkar; Debarati Shome; Philipp Reichert; Calin Manta; Stefanie Gryzik; et al. (Cells, 2024)
Current treatment strategies for multiple myeloma (MM) are highly effective, but most patients develop relapsed/refractory disease (RRMM). The anti-CD38/CD3xCD28 trispecific antibody SAR442257 targets CD38 and CD28 on MM cells and co-stimulates CD3 and CD28 on T cells (TCs). We evaluated different key aspects such as MM cells and T cells avidity interaction, tumor killing, and biomarkers for drug potency in three distinct cohorts of RRMM patients. We found that a significantly higher proportion of RRMM patients (86%) exhibited aberrant co-expression of CD28 compared to newly diagnosed MM (NDMM) patients (19%). Furthermore, SAR442257 mediated significantly higher TC activation, resulting in enhanced MM killing compared to bispecific functional knockout controls for all relapse cohorts (Pearson’s r = 0.7). Finally, patients refractory to anti-CD38 therapy had higher levels of TGF-β (up to 20-fold) compared to other cohorts. This can limit the activity of SAR442257. Vactoserib, a TGF-β inhibitor, was able to mitigate this effect and restore sensitivity to SAR442257 in these experiments. In conclusion, SAR442257 has high potential for enhancing TC cytotoxicity by co-targeting CD38 and CD28 on MM and CD3/CD28 on T cells.